Pengaruh Motivasi Dan Semangat Kerja Karyawan Dalam Upaya Meningkatkan Produktivitas Pada PT. X Jakarta - Aini, Marina; Sari, Imelda; Astuti, Dewi (Politeknik Negeri Ambon, 2024)
PT. X is an official distributor company which operates in the field of providing laptop products and providing various kinds of computer hardware and software. The increasing mobility of people and the importance of devices to support their productivity has made the company want to increase PT. X's sales turnover, which is one of the company's goals. However, efforts to increase sales turnover can cause higher levels of employee pressure and decreased work morale. The increasing level of employee pressure and decreasing work morale at PT. X could be a negative impact of the company's efforts to increase sales turnover. Increased stress and decreased morale can become a dangerous cycle for a company. Increasing employee motivation and morale is an important responsibility for the leadership of an organization. A visionary leader needs to create a conducive organizational climate to maintain the morale and work dedication of his team members. The main goal of effective leadership is to inspire and motivate employees. This research uses quantitative methods, the samples in this research are all employees in the IT and Service division of PT. X, totaling 30 people. The research results show that based on the presentation of the results that have been presented, it can be seen that the Fcount value is more than Ftable (3.354) with a significance level of <0.05, so it can be concluded that the motivation and work enthusiasm variables together have an effect on productivity (Fcount 14.101 > Ftable 3.354). Bearti H3 is accepted, motivation and work enthusiasm have a simultaneously positive and significant influence on productivity.